2011
DOI: 10.3171/2011.9.focus11178
|View full text |Cite
|
Sign up to set email alerts
|

Chronic traumatic encephalopathy in an Iraqi war veteran with posttraumatic stress disorder who committed suicide

Abstract: Following his discovery of chronic traumatic encephalopathy (CTE) in football players in 2002, Dr. Bennet Omalu hypothesized that posttraumatic stress disorder (PTSD) in military veterans may belong to the CTE spectrum of diseases. The CTE surveillance at the Brain Injury Research Institute was therefore expanded to include deceased military veterans diagnosed with PTSD. The authors report the case of a 27-year-old United States Marine Corps (USMC) Iraqi war veteran, an amphibious assault vehicle crewm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
177
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(184 citation statements)
references
References 29 publications
6
177
0
1
Order By: Relevance
“…71 Since the identification of CTE in a former professional American football player in 2005, 72 and additional intensive pathological studies, this condition has gained widespread public attention, and has now been identified in brains of former ice hockey, baseball, rugby and soccer players, 73 wrestlers, 74 and military veterans. 75,76 The prevalence and incidence of CTE in amateur and professional athletes is still unknown, adding to difficulties in discussing its epidemiology and population risks for athletes. Although CTE is primarily considered to be a neurodegenerative disease that sometimes results from a career of either collegiate or professional contact sports, cases of CTE have been reported in high school athletes.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…71 Since the identification of CTE in a former professional American football player in 2005, 72 and additional intensive pathological studies, this condition has gained widespread public attention, and has now been identified in brains of former ice hockey, baseball, rugby and soccer players, 73 wrestlers, 74 and military veterans. 75,76 The prevalence and incidence of CTE in amateur and professional athletes is still unknown, adding to difficulties in discussing its epidemiology and population risks for athletes. Although CTE is primarily considered to be a neurodegenerative disease that sometimes results from a career of either collegiate or professional contact sports, cases of CTE have been reported in high school athletes.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…3,7 Moreover, CTE has been found in nonathletes who have experienced repetitive head impacts, including military service members, 2,8,9 persons with medical conditions such as epilepsy and autism, and victims of physical abuse. 2,10 All patients with neuropathologically confirmed CTE reported to date have had a history of brain trauma, typically from repetitive mild or subconcussive head impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, we are unable to predict the probability of long-term problems for a given number of sport-related concussions. Some athletes who have sustained multiple traumatic injuries to the brain over long careers in boxing, American football, and other sports have pathologic changes in the brain such as the deposition of beta-amyloid and phosphorylated tau [15][16][17][18][19][20][21][22][23][24]. This condition has become known as chronic traumatic encephalopathy.…”
Section: Commentarymentioning
confidence: 99%